Exploring the Knowledge, Attitude, and Practices of Second and Thirdhand Smoke Among Smokers and Nonsmokers: A Web Based Survey - Charu Mohan Marya; Neha Jha; Pratibha Taneja; Ruchi Nagpal; Sakshi Kataria; Jeevan Josh (Journal of Indian Association of Public Health Dentistry)
Aim: The aim of this study was to assess the knowledge, attitude, and practices of secondhand smoke (SHS) and thirdhand smoke (THS) among smokers and nonsmokers. Methodology: A cross-sectional web-based questionnaire study was conducted among the general population (both smokers and nonsmokers). A structured questionnaire was developed assessing the knowledge (18 items) and attitude and practices (11 items) of smokers and nonsmokers regarding SHS and THS. Through WhatsApp groups, the questionnaire was circulated to 330 subjects in total. Comparative evaluation of item responses was performed using the Statistical Package for the Social Sciences software (v21, IBM Corp., Armonk, NY, USA). Inferential statistics was done using the Chi-square test to find out the association among categorical variables. The level of statistical significance was set at P < 0.05. Results: A total of 270 participants registered their responses. Knowledge regarding SHS and THS was found to be higher among nonsmokers. Nonsmokers were found to be significantly more attentive, aware, and cautious from SHS and THS as compared to smokers. Conclusion: Satisfactory knowledge levels regarding second- and thirdhand exposure were seen among smokers and nonsmokers, yet its applicability in terms of prevention from SHS and THS was limited. Thus, there is an urgent need to develop and implement some interventions to increase the awareness toward secondhand and thirdhand and also to improve the practices of smokers to prevent the general public from this harmful exposure.